PROFILING OVERVIEW IN FORENSIC INVESTIGATIONS - Tolbaru , Carmina-Elena (International Journal of Legal and Social Order, 2024)
The profiling investigation has great applicability in the field of forensics, providing relevant information regarding the psycho-behavioral interpretation of the criminal, in the context of the dynamics of the criminal act. In order to interpret criminal behavior and outline the psychological profile, the exploratory skills of the lawman stand out on the "game board", in a direct confrontation with the criminal. Although, from a legal point of view, in the criminal legislation in Romania, profiling is not found among the means of evidence, this investigative tool is mainly used in crimes of great violence, which present atypical elements